Molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material, preparation method thereof, lithium-sulfur battery positive electrode and lithium-sulfur battery
By using molybdenum disulfide nanosheets/nitrogen-doped bamboo-like carbon fiber tubes/sulfur composite materials, the problems of low conductivity, volume expansion and shuttle effect in lithium-sulfur batteries were solved, achieving high efficiency in cycle stability and rate performance.
Patent Information
- Application Number
- CN202510878790.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-06-27
AI Technical Summary
Lithium-sulfur batteries suffer from low conductivity, volume expansion, and shuttle effect caused by polysulfide dissolution in the cathode material, which affect their cycle stability and battery life.
A composite material of molybdenum disulfide nanosheets/nitrogen-doped bamboo-like carbon fiber tubes/sulfur is used. The nitrogen-doped bamboo-like carbon fiber tubes provide conductivity and physical adsorption, while the molybdenum disulfide nanosheets provide chemical adsorption and catalytic active sites, which synergistically suppress the shuttle effect.
It significantly improves the cycle stability and rate performance of lithium-sulfur batteries, enhances the redox kinetics of polysulfides, and suppresses volume expansion and shuttle effect.
Smart Images

Figure CN120824334A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials for lithium-sulfur batteries, and particularly relates to a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material and a preparation method thereof, as well as a lithium-sulfur battery positive electrode and a lithium-sulfur battery. Background Art
[0002] The tremendous progress of society and technology has brought about a crisis in non-renewable energy sources and irreversible environmental pollution. Therefore, the abundance of renewable energy has attracted continuous attention. Lithium-ion batteries are widely used in all aspects of our lives (such as smartphones, laptops, electric vehicles, etc.), greatly changing human life. However, with the further development of electrical products and the rapid growth of people's demand, the inherent shortcomings of lithium-ion batteries have begun to emerge, such as insufficient energy density and power density. In order to continuously promote the development of energy storage systems and meet people's demand for high energy density and high power density energy storage devices, researchers have been forced to seek other solutions.
[0003] Lithium-sulfur batteries have a high theoretical capacity (1675 mA h g) due to the two-electron conversion reaction from S to Li2S. -1 ) and high energy density (2600Wh kg -1 ) has aroused widespread research interest and is considered to be one of the most promising next-generation energy storage systems. In addition, the abundant natural reserves of sulfur, its harmlessness to the environment and its low cost also make lithium-sulfur batteries more commercially advantageous in practical applications. Despite these significant advantages of lithium-sulfur batteries, their widespread application is still hindered by some factors. For example: (1) The low conductivity of the active material elemental sulfur in the positive electrode and the Li2S / Li2S2 product generated during the charge and discharge process (conductivity ≈ 5×10 -30 S cm -1 ) hinders the transport of electrons and ions during charge and discharge, reducing the electrochemical reaction kinetics of the active material sulfur; (2) The densities of S8 and Li2S are 2.07 and 1.66 g cm, respectively. -3 , the density difference causes the positive electrode to expand severely in volume (~80%) during the cycle reaction; (3) the lithium polysulfide produced during the electrochemical reaction has a high solubility in the electrolyte, resulting in a serious shuttle effect, which leads to the gradual attenuation of battery capacity and shortens the battery life.
[0004] In lithium-sulfur batteries, adding transition metal compounds that adsorb polysulfides and electrocatalyze electrode reactions to the cathode material is a promising approach. Two-dimensional (2D) layered transition metal compounds have attracted significant interest due to their large surface area, strong chemical adsorption of polysulfides, and weak van der Waals forces between individual molecules. Furthermore, transition metal sulfides can promote the conversion of polysulfides, serving as active sites for catalyzing the formation of polysulfide intermediates. This phenomenon stems from the strong electronegativity of the sulfur atoms in the metal sulfide, which allows them to capture electrons from the transition metal.
[0005] Lin et al. synthesized c-MoS2 nanosheets with sulfur vacancies and high specific surface area, which provided additional redox reaction sites for polysulfides during the operation of lithium-sulfur batteries (J. Mater. Chem. A, 11, 2023, 8265-8276). However, the cycling stability of these sulfur supports still needs to be improved in the practical application of lithium-sulfur batteries. Summary of the Invention
[0006] To solve the above technical problems, the present invention provides a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material and its preparation method. The nitrogen-doped bamboo-like carbon fiber tube not only has conductive and connecting functions, but also provides a certain physical adsorption effect for polysulfides. In addition, nitrogen atoms can effectively capture soluble polysulfides through chemical reactions, thereby synergizing with the hollow porous structure. At the same time, the ultra-thin molybdenum disulfide nanosheet containing the 1T metal phase exposes more active sites while improving conductivity, which greatly enhances its contribution to the redox kinetics of sulfur species and fully suppresses the shuttle effect, thereby improving the performance of lithium-sulfur batteries.
[0007] The present invention also provides a lithium-sulfur battery positive electrode and a lithium-sulfur battery. The lithium-sulfur battery positive electrode is prepared using the molybdenum disulfide nanosheet-modified nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material described in the present invention as an active material, and then assembled into a lithium-sulfur battery. The lithium-sulfur battery has good cycle stability and rate performance.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] The present invention provides a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material. The composition and morphology of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material are as follows: the surface of a hollow bamboo-like nitrogen-doped bamboo-like carbon fiber tube is coated with flaky molybdenum disulfide nanosheets, and sulfur is loaded on the flaky molybdenum disulfide nanosheets.
[0010] The present invention also provides a method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material, the preparation method comprising the following steps:
[0011] (1) Melamine and aluminum are mixed and reacted at a high temperature of 900 to 1500° C. for 0.5 to 4 hours under the protection of an inert gas. The resulting reactant is soaked in an inorganic acid solution for 2 to 24 hours, washed, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material having a hollow bamboo-like structure.
[0012] (2) dispersing the nitrogen-doped bamboo-like carbon fiber tube material, thioacetamide, sodium molybdate, and urea in a solvent, performing a solvent thermal reaction, and calcining the resulting reactant in a reducing atmosphere to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material;
[0013] (3) Sulfur is fumigated on the molybdenum sulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material.
[0014] In step (1), the usage ratio of melamine to aluminum is 20.0 g: (0.1-0.5) g.
[0015] In step (1), the concentration of the inorganic acid solution is 1 to 8 mol L -1 , preferably 3 to 4 mol L -1 ; The inorganic acid solution is one or more of sulfuric acid, nitric acid, hydrochloric acid and phosphoric acid; the soaking reaction temperature is 5 to 80°C, preferably 25 to 50°C; the soaking time is preferably 12 to 18 hours.
[0016] In step (1), the high temperature reaction condition is preferably 1100-1200° C. for 2-3 hours.
[0017] In step (1), the inert atmosphere is nitrogen or argon.
[0018] In step (2), the usage ratio of the nitrogen-doped bamboo-shaped carbon fiber tube material to thioacetamide, sodium molybdate, and urea is 0.05 g: (0.05-0.35) g: (0.08-0.5) g: (0.01-0.1) g.
[0019] In step (2), the solvent is a mixed solvent of water and any one or more of isopropyl alcohol, ethylene glycol, N,N-dimethylformamide or dimethyl sulfoxide, wherein the volume percentage of water in the mixed solvent is 3% to 45%, preferably 10% to 15%.
[0020] In step (2), the solvent thermal reaction conditions are 160-240° C. for 6-36 hours, preferably 180-200° C. for 20-30 hours; the calcination conditions are: heating and keeping warm at 500-900° C. for 1-5 hours; the reducing atmosphere is a mixture of hydrogen and argon, wherein the volume percentage of hydrogen is 3-10%, preferably 5%.
[0021] In step (3), the heating sulfur fumigation condition is 125-185° C. for 6-48 hours, preferably 150-170° C. for 12-36 hours;
[0022] In step (3), the mass ratio of molybdenum disulfide nanosheets / nitrogen-doped bamboo-shaped carbon fiber tubes to sulfur powder is 1:1.5-3.5.
[0023] In step (3), the inert atmosphere is nitrogen or argon.
[0024] The present invention also provides a lithium-sulfur battery positive electrode, which is prepared using the molybdenum disulfide nanosheets / nitrogen-doped bamboo-shaped carbon fiber tubes / sulfur composite material of the present invention as an active material.
[0025] The present invention also provides a lithium-sulfur battery, which uses the lithium-sulfur battery positive electrode of the present invention as the positive electrode. It has good stability and is -1 After 500 cycles at the same current density, the cathode capacity is still as high as 403 mAh g -1 above.
[0026] The present invention provides a method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material. First, melamine is used as a carbon source and aluminum metal is used as a catalyst. A high-temperature catalytic reaction is performed, followed by acid treatment, to produce hollow, bamboo-like nitrogen-doped bamboo-like carbon fiber tubes with a multi-layered structure. The nitrogen-doped bamboo-like carbon fiber tubes are then mixed with thioacetamide, sodium molybdate, and urea for a solvothermal reaction. The mixture is then calcined at high temperature to produce nitrogen-doped bamboo-like carbon fiber tubes coated with molybdenum disulfide nanosheets. Finally, sulfur is loaded on the surface of the molybdenum disulfide nanosheets using a sulfur melt diffusion strategy to produce the molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material.
[0027] The chemical reaction formula involved in the above reaction process is expressed as follows:
[0028] C3H6N6→3C+3N2↑+3H2↑
[0029] CO(NH2)2+3H2O→NH4HCO3+NH3·H2O
[0030] 7CH3CSNH2+3Na2MoO4+2NH3·H2O+3H2O→6CH3COONa+3MoS2
[0031] +CH3COONH4+6NH3+(NH4)2SO3
[0032] The molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material provided by the present invention is simple to synthesize. Its hollow bamboo-like tubular structure provides abundant voids to buffer volume changes, enabling efficient electron transfer, which helps increase sulfur loading while providing a buffer for sulfur volume expansion. Furthermore, the nanosheet-like molybdenum disulfide has numerous exposed active sites, facilitating the physical confinement and chemical adsorption of polysulfides, accelerating electrochemical reaction kinetics. Using this material as the positive electrode of a lithium-sulfur battery significantly improves its cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an SEM image of the nitrogen-doped bamboo-shaped carbon fiber tube prepared in Example 1;
[0034] Figure 2 TEM image of the nitrogen-doped bamboo-shaped carbon fiber tube prepared in Example 1;
[0035] Figure 3 This is the XRD pattern of the nitrogen-doped bamboo-shaped carbon fiber tube prepared in Example 1;
[0036] Figure 4 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube composite material prepared in Example 1;
[0037] Figure 5 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 1;
[0038] Figure 6 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 2;
[0039] Figure 7 This is an SEM image of the nitrogen-doped bamboo-shaped carbon fiber tube material prepared in Example 3;
[0040] Figure 8 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube composite material prepared in Example 3;
[0041] Figure 9 TEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube composite material prepared in Example 3;
[0042] Figure 10 This is the XRD pattern of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube composite material prepared in Example 3;
[0043] Figure 11 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 3;
[0044] Figure 12 TEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material prepared in Example 3;
[0045] Figure 13 This is the XRD pattern of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 3;
[0046] Figure 14 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 4;
[0047] Figure 15 This is an SEM image of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 4;
[0048] Figure 16 The carbon nanotube material prepared using the iron sheet as the catalyst in Comparative Example 1;
[0049] Figure 17 The carbon nanotube material prepared using the cobalt sheet as the catalyst in Comparative Example 1;
[0050] Figure 18 The carbon nanotube material prepared using the nickel sheet as a catalyst in Comparative Example 1;
[0051] Figure 19 The lithium-sulfur battery made of the molybdenum disulfide nanosheets / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material prepared in Example 3 as the positive electrode material was -1 Test results of 100 cycles at the current density;
[0052] Figure 20 The lithium-sulfur battery prepared by using the molybdenum disulfide nanosheets / nitrogen-doped bamboo-shaped carbon fiber tube material / sulfur composite material as the positive electrode material in Example 3 was -1 Test results of 500 cycles at the same current density. DETAILED DESCRIPTION
[0053] The present invention is described in detail below with reference to the embodiments.
[0054] Example 1
[0055] A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material comprises the following steps:
[0056] (1) Place 20.0g of melamine and 0.1g of aluminum sheet in a high-temperature tube furnace and react at 1500℃ for 0.5h under nitrogen atmosphere. Then soak it in 60mL of 1.0mol L -1 The mixture was reacted in a sulfuric acid solution at 5°C for 24 hours, washed with deionized water, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material. Figure 1 As shown, Figure 2 The TEM image and the XRD pattern are as follows Figure 3 As shown;
[0057] (2) 0.05g nitrogen-doped bamboo-like carbon fiber tube material, 0.05g thioacetamide, 0.08g sodium molybdate and 0.01g urea were dispersed in a mixed solvent of water and isopropanol with a water volume content of 3%, reacted at 160°C for 36h, washed with deionized water and dried, and then reacted at 500°C for 5h in a hydrogen-argon mixed gas with a hydrogen volume percentage of 5% to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube composite material. The SEM image of the product is shown in FIG. Figure 4 As shown in the figure, it can be seen that the MoS2 nanosheets are evenly distributed on the surface of the nitrogen-doped bamboo-like carbon fiber tube;
[0058] (3) 0.1g of molybdenum disulfide nanosheets / nitrogen-doped bamboo-like carbon fiber tube material was mixed evenly with 0.15g of sulfur powder, and transferred to a polytetrafluoroethylene vial filled with argon. The mixture was reacted at 125°C for 48h under an argon atmosphere to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material. The SEM image is shown below. Figure 5 As shown, it can be seen from the figure that sulfur is uniformly loaded on the nanotubes.
[0059] Example 2
[0060] A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material comprises the following steps:
[0061] (1) Place 20.0g of melamine and 0.2g of aluminum sheet in a high-temperature tube furnace and react at 1300℃ for 1h under nitrogen atmosphere. Then soak it in 60mL of 3.0mol L -1 The mixture was reacted in a nitric acid solution at 20°C for 18 h, washed with deionized water, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material;
[0062] (2) 0.05 g of nitrogen-doped bamboo-like carbon fiber tube material, 0.1 g of thioacetamide, 0.15 g of sodium molybdate, and 0.03 g of urea were dispersed in a mixed solvent of water and ethylene glycol with a water volume content of 10%, reacted at 180 ° C for 30 h, washed with deionized water, and dried, and then reacted at 600 ° C for 4 h in a hydrogen-argon mixture with a hydrogen volume percentage of 5% to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube composite material;
[0063] (3) 0.1g of MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material was mixed evenly with 0.2g of sulfur powder, and transferred to a polytetrafluoroethylene vial filled with argon. The mixture was reacted at 140°C for 40h under argon atmosphere to obtain MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material. The SEM image is shown below. Figure 6 As shown, it can be seen from the figure that sulfur is uniformly loaded on the nanotubes.
[0064] Example 3
[0065] A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material comprises the following steps:
[0066] (1) Place 20.0g of melamine and 0.3g of aluminum sheet in a high temperature tube furnace and react at 1200℃ for 2h under nitrogen atmosphere. Then soak it in 60mL of 4.0mol L -1 The mixture was reacted in a hydrochloric acid solution at 50°C for 12 hours, washed with deionized water, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material. The SEM image of the prepared nitrogen-doped bamboo-like carbon fiber tube is shown in FIG. Figure 7 As shown;
[0067] (2) 0.05g nitrogen-doped bamboo-like carbon fiber tube material, 0.15g thioacetamide, 0.25g sodium molybdate and 0.04g urea were dispersed in a mixed solvent of water and N,N-dimethylformamide with a water volume content of 15%, reacted at 200℃ for 20h, washed with deionized water and dried, and then reacted at 700℃ for 3h in a hydrogen-argon mixed gas with a hydrogen volume percentage of 5% to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube composite material. The SEM image of the product is shown in Figure 2. Figure 8 As shown in the TEM image Figure 9 As shown in the figure, it can be seen that the molybdenum disulfide nanosheets are evenly distributed on the surface of the nitrogen-doped bamboo-like carbon fiber tube and the hollow bamboo-like structure; the XRD pattern of the product is shown in Figure 10 As shown, the characteristic diffraction peak of molybdenum disulfide can be seen from the figure;
[0068] (3) 0.1g of MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material was mixed evenly with 0.25g of sulfur powder, and transferred to a polytetrafluoroethylene vial filled with argon. The mixture was reacted at 150°C for 36h under argon atmosphere to obtain MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material. The SEM image is shown below. Figure 11 As shown in the TEM image Figure 12 As shown in the figure, it can be seen that sulfur is uniformly loaded on the molybdenum disulfide nanosheets / nitrogen-doped bamboo-like carbon fiber tubes, and the molybdenum disulfide nanosheets are uniformly distributed on the outer layer of the nitrogen-doped bamboo-like carbon fiber tubes; the XRD pattern of the product is shown in Figure 13 As shown, characteristic diffraction peaks of molybdenum disulfide and sulfur can be seen from the figure;
[0069] Example 4
[0070] A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material comprises the following steps:
[0071] (1) Place 20.0g of melamine and 0.4g of aluminum sheet in a high-temperature tube furnace and react at 1100℃ for 3h under nitrogen atmosphere. Then soak it in 60mL of 6.0mol L -1 The mixture was reacted in a phosphoric acid solution at 65°C for 6 h, washed with deionized water, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material.
[0072] (2) 0.05 g of nitrogen-doped bamboo-like carbon fiber tube material, 0.25 g of thioacetamide, 0.35 g of sodium molybdate, and 0.08 g of urea were dispersed in a mixed solvent of water and ethylene glycol with a water volume content of 30%, reacted at 220 ° C for 12 h, washed with deionized water, and dried, and then reacted at 800 ° C for 2 h in a hydrogen-argon mixture with a hydrogen volume percentage of 5% to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube composite material;
[0073] (3) 0.1g of MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material was mixed evenly with 0.3g of sulfur powder, and transferred to a polytetrafluoroethylene vial filled with argon. The mixture was reacted at 170°C for 12h under argon atmosphere to obtain MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material. The SEM image is shown below. Figure 14 As shown, it can be seen from the figure that sulfur is uniformly loaded on the nanotubes.
[0074] Example 5
[0075] A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material comprises the following steps:
[0076] (1) Place 20.0g of melamine and 0.5g of aluminum sheet in a high-temperature tube furnace and react at 900℃ for 4h under nitrogen atmosphere. Then soak it in 60mL of 8.0mol L -1 The mixture was reacted in a sulfuric acid solution at 80°C for 2 h, washed with deionized water, and dried to obtain a nitrogen-doped bamboo-like carbon fiber tube material.
[0077] (2) 0.05 g of nitrogen-doped bamboo-like carbon fiber tube material, 0.35 g of thioacetamide, 0.5 g of sodium molybdate, and 0.1 g of urea were dispersed in a mixed solvent of water and dimethyl sulfoxide with a water volume content of 45%, reacted at 240 ° C for 6 h, washed with deionized water, and dried, and then reacted at 900 ° C for 1 h in a hydrogen-argon mixture with a hydrogen volume percentage of 5% to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube composite material;
[0078] (3) 0.1g of MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material was mixed evenly with 0.35g of sulfur powder, and transferred to a polytetrafluoroethylene vial filled with argon. The mixture was reacted at 185°C for 6h under argon atmosphere to obtain MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tube material / sulfur composite material. The SEM image is shown below. Figure 15 As shown, it can be seen from the figure that sulfur is uniformly loaded on the nanotubes.
[0079] Comparative Example 1
[0080] Place 20.0g of melamine and 0.5g of iron sheet, nickel sheet or cobalt sheet in a high temperature tube furnace and react at 1100℃ for 4h under nitrogen atmosphere. Then soak it in 60mL of 5.0mol L -1 The nitrogen-doped carbon nanotube material was obtained by reacting in a sulfuric acid solution at 80°C for 2 h, washing with deionized water, and drying. The SEM image of the obtained material is shown in FIG. Figure 16-18 As shown in the figure, it can be seen that the diameter of the nanotubes is small, there is no bamboo-like shape, and the thickness is uneven.
[0081] Application Example 1
[0082] Application of a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material in lithium-sulfur batteries
[0083] The final product of Example 3, molybdenum disulfide nanosheets / nitrogen-doped bamboo-like carbon fiber tubes / sulfur composite material, was used as the positive electrode active material of the lithium-sulfur battery. It was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a weight ratio of 7.5:1.5:1, and prepared into a uniform slurry using N-methylpyrrolidone (NMP) as a solvent. The slurry was coated on aluminum foil, and the prepared coating was transferred to an oven and dried at 60°C for 6 hours. Then, the sample was transferred to a vacuum drying oven and vacuum dried at 60°C for 12 hours, then rolled with a tablet press and cut into pieces. The lithium sheet was used as the counter electrode, the electrolyte was a mixed organic solvent containing 1M lithium bis(trifluoromethanesulfonyl)imide (LITFSI), and the mixed organic solvent was a mixed solvent composed of 1,3-dioxolane (DOL) and dimethyl ether (DME) in a volume ratio of 1:1. LiNO3 with a mass fraction of 2% was added as an electrolyte additive, and a polypropylene film (Celgard240) was used as the battery separator. The lithium-sulfur battery was assembled under an argon atmosphere.
[0084] The charge and discharge performance test was carried out using a battery tester. The obtained lithium-sulfur battery positive electrode material was -1 The results of the cycling stability test under current density are shown in the attached Figure 19 As shown, at 1.0Ag -1 The results of the cycling stability test at the current density are shown in the attached Figure 20 As shown in the figure, the MoS2 nanosheets / nitrogen-doped bamboo-like carbon fiber tubes / sulfur-lithium-sulfur battery has good cycle stability. -1 The cathode capacity reaches 655 mAh g after 100 cycles at the same current density. -1 , at 1.0Ag -1 After 500 cycles at the same current density, the cathode capacity is still as high as 403 mAh g -1 .
[0085] The detailed description of a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material and its preparation method, as well as a lithium-sulfur battery positive electrode and a lithium-sulfur battery with reference to the above examples is illustrative rather than restrictive. Several embodiments can be listed within the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should be within the scope of protection of the present invention.
Claims
1. A molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material, characterized in that: The composition and morphology of the molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material are as follows: the surface of the hollow bamboo-like nitrogen-doped bamboo-like carbon fiber tube is coated with flaky molybdenum disulfide nanosheets, and the flaky molybdenum disulfide nanosheets are loaded with sulfur nanoparticles.
2. A method for preparing a molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material, characterized in that: The preparation method comprises the following steps: (1) Melamine and aluminum are mixed and reacted at a high temperature of 900 to 1500° C. for 0.5 to 4 hours under the protection of an inert gas. The resulting reactant is soaked in an inorganic acid solution for 2 to 24 hours, washed, and dried to obtain a nitrogen-doped bamboo-shaped carbon fiber tube material; (2) dispersing the nitrogen-doped bamboo-like carbon fiber tube material, thioacetamide, sodium molybdate, and urea in a solvent, performing a solvent thermal reaction, and calcining the resulting reactant in a reducing atmosphere to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material; (3) Sulfur is fumigated on the molybdenum sulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube material to obtain a molybdenum disulfide nanosheet / nitrogen-doped bamboo-like carbon fiber tube / sulfur composite material.
3. The preparation method according to claim 2, characterized in that In step (1), the usage ratio of melamine to aluminum is 20g:(0.1-0.5)g.
4. The preparation method according to claim 2, characterized in that In step (1), the inorganic acid is at least one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid, and the concentration of the solution is 1 to 8 mol L -1 .
5. The preparation method according to claim 2, characterized in that In step (2), the ratio of the nitrogen-doped bamboo-shaped carbon fiber tube material to thioacetamide, sodium molybdate, and urea is 0.05 g: (0.05~0.35)g: (0.08~0.5)g: (0.01~0.1)g.
6. The preparation method according to claim 2, characterized in that In step (2), the solvent is a mixed solvent of water and any one or more of isopropyl alcohol, ethylene glycol, N,N-dimethylformamide or dimethyl sulfoxide, wherein the volume percentage of water in the mixed solvent is 3% to 45%.
7. The preparation method according to claim 2, characterized in that In step (2), the solvent thermal reaction conditions are 160-240° C. for 6-36 hours; the calcination conditions are 500-900° C. for 1-5 hours; and the reducing atmosphere is a mixture of hydrogen and argon, wherein the volume percentage of hydrogen is 3-10%.
8. The preparation method according to claim 2, characterized in that In step (3), the heating and sulfur fumigation conditions are 125-185° C. and maintained for 6-48 hours; the mass ratio of molybdenum disulfide nanosheets / nitrogen-doped bamboo-shaped carbon fiber tubes to sulfur powder is 1:1.5-3.
5.
9. A lithium-sulfur battery positive electrode, characterized in that: The molybdenum disulfide nanosheet / nitrogen-doped bamboo-shaped carbon fiber tube / sulfur composite material according to claim 1 is used as the active material for preparation.
10. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery uses the lithium-sulfur battery positive electrode according to claim 9 as the positive electrode.
Citation Information
Patent Citations
Preparation method of carbon-sulfur composite material for lithium ion battery carbon cathode material
CN102208608A
Metal nickel / nitrogen-doped carbon nanotube and lithium-sulfur battery composite positive electrode material thereof
CN111211300A
Bamboo-shaped oxide and carbon nanotube material as well as preparation method and application thereof
CN116988095A
Nitrogen-doped carbon nanotube packaged molybdenum nitride nanoparticle / sulfur composite material, preparation method thereof and application of nitrogen-doped carbon nanotube packaged molybdenum nitride nanoparticle / sulfur composite material in lithium-sulfur battery
CN117117128A